Electron Push-Pull Effect of Benzotrithiophene-Based Covalent Organic Frameworks on the Photocatalytic Degradation of Pharmaceuticals and Personal Care Products - Hongguang Guo; Jiaqin He; Yixi Guo; Yunxi Chang; Haidong Ju; Yizhou Li (Molecules)
A covalent organic framework (COF) has emerged as a promising photocatalyst for the removal of pharmaceutical and personal care product (PPCP) contaminants; however, high-performance COF photocatalysts are still scarce. In this study, three COF photocatalysts were successfully synthesized by the condensation of benzo[1,2-b:3,4-b′:5,6-b′′]trithiophene-2,5,8-tricarbaldehyde (BTT) with 4,4′,4′′-(1,3,5-triazine-2,4,6-triyl)trianiline (TAPT), 1,3,5-Tris(4-aminophenyl)benzene (TAPB), and 4,4′,4′′-nitrilotris(benzenamine) (TAPA), namely, BTT-TAPA, BTT-TAPB, and BTT-TAPT, respectively. The surface areas of BTT-TAPA, BTT-TAPB, and BTT-TAPT were found to be 800.46, 1203.60, and 1413.58 cm2∙g−1, respectively, providing abundant active sites for photocatalytic reactions. Under visible-light irradiation, BTT-TAPT exhibited the highest removal rate of tetracycline (TC), reaching 82.7% after 240 min. The superior photocatalytic performance of BTT-TAPT was attributed to its large specific surface area and the strong electron-acceptor properties of the triazine group. Electron paramagnetic resonance capture experiments and liquid chromatograph mass spectrometer analysis confirmed that superoxide radicals played a pivotal role in the degradation of TC and ciprofloxacin. Moreover, BTT-TAPT exhibited high stability and reproducibility during the photocatalytic degradation process. This study confirms that BTT-based COFs are a class of promising photocatalysts for the degradation of PPCPs in water, and their performance can be further optimized by tuning the structure and composition of the frameworks.